2021
DOI: 10.3390/molecules26175293
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Porous Carbon Materials Derived from Graphene Oxide/Melamine Resin Composites for CO2 Adsorption

Abstract: CO2 adsorption in porous carbon materials has attracted great interests for alleviating emission of post-combustion CO2. In this work, a novel nitrogen-doped porous carbon material was fabricated by carbonizing the precursor of melamine-resorcinol-formaldehyde resin/graphene oxide (MR/GO) composites with KOH as the activation agent. Detailed characterization results revealed that the fabricated MR(0.25)/GO-500 porous carbon (0.25 represented the amount of GO added in wt.% and 500 denoted activation temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…The XPS spectrum of N 1s could be fitted as pyridinic-N, pyrrole-N, and quaternary-N at 398.3, 399.8, and 401.3 eV, respectively (Figure 3f). 10,22,27 The signal peak intensity was highly correlated to the carbonization temperature and the stability of N types. With the increase in carbonization temperature, the contents of pyridine-N and pyrrolic-N decreased, while that of the quaternary-N increased (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…The XPS spectrum of N 1s could be fitted as pyridinic-N, pyrrole-N, and quaternary-N at 398.3, 399.8, and 401.3 eV, respectively (Figure 3f). 10,22,27 The signal peak intensity was highly correlated to the carbonization temperature and the stability of N types. With the increase in carbonization temperature, the contents of pyridine-N and pyrrolic-N decreased, while that of the quaternary-N increased (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the binary co-doping technique, the results did not improve significantly compared to the studies mentioned previously. [3,36] This implies that the type of porous carbon used is one of the key factors to consider as some are more effective than others, as opposed to the level of doping and number of heteroatom dopants. It would be worthwhile to determine the effects of co-doping for activated carbons that previously delivered the best CO 2 adsorption abilities, including those obtained from graphene oxide and hydrochar precursors.…”
Section: Co 2 Adsorptionmentioning
confidence: 99%
“…[39,40] Over the recent decades, researchers have investigated N-doped carbon-based materials for energy conversion and storage applications. [36] Copyright 2021, the Authors. Published by MDPI.…”
Section: Energy Conversion and Storage Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Yuan and co-workers reported nitrogen-doped porous carbon employing melamine-resorcinol-formaldehyde resin and graphene oxide. This material had shown a CO 2 adsorption capacity of 5.21 mmol/g at 298 K at 5 bar pressure . In other attempts, graphene-like morphology/graphene-based nanomaterials were also synthesized and explored for CO 2 adsorption. For example, graphene-like multiscale microporous carbon nanosheets were synthesized by Shi et al, which provided a CO 2 adsorption capacity of 6.32 mmol/g at 273 K/1 bar .…”
Section: Introductionmentioning
confidence: 99%